2020
DOI: 10.3389/fpls.2020.00564
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Interaction Among Phytochrome, Ethylene and Abscisic Acid Signaling During Dark-Induced Senescence in Arabidopsis thaliana

Abstract: Leaf senescence is induced by various internal and external stimuli. Dark-induced senescence has been extensively investigated, but the detailed mechanism underlying it is not well understood. The red light/far-red light receptor phytochrome B and its downstream transcription factors, PYHTOCHROME INTERACTING FACTORs (PIFs) 4 and 5, are known to play an important role in dark-induced senescence. Furthermore, the senescence-inducing phytohormones, ethylene and abscisic acid (ABA) are reported to be involved in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 64 publications
2
31
0
Order By: Relevance
“…SAGs have been regulated by various environmental signals which include both abiotic and biotic stresses indicating various cross-talks between SAGs and stress responses (Lim et al ., 2007). Genes such as SAG12, SAG29 , and ORE1 play an important role in submergence mediated recovery by influencing senescence and chlorophyll breakdown in Arabidopsis (Huynh et al ., 2005, Seo et al ., 2011a, Yeung et al ., 2018, Bengoa Luoni et al ., 2019, Ueda et al ., 2020). To understand the molecular mechanism underlying leaf senescence in miR775 transgenic and galt9 lines, we compared the expression level of SAG12, SAG29 , and ORE1 during submergence stress.…”
Section: Resultsmentioning
confidence: 99%
“…SAGs have been regulated by various environmental signals which include both abiotic and biotic stresses indicating various cross-talks between SAGs and stress responses (Lim et al ., 2007). Genes such as SAG12, SAG29 , and ORE1 play an important role in submergence mediated recovery by influencing senescence and chlorophyll breakdown in Arabidopsis (Huynh et al ., 2005, Seo et al ., 2011a, Yeung et al ., 2018, Bengoa Luoni et al ., 2019, Ueda et al ., 2020). To understand the molecular mechanism underlying leaf senescence in miR775 transgenic and galt9 lines, we compared the expression level of SAG12, SAG29 , and ORE1 during submergence stress.…”
Section: Resultsmentioning
confidence: 99%
“…Leaf yellowing, a distinct initial symptom of leaf senescence, is caused by chlorophyll depletion [ 51 ]. This reduction of chlorophyll is a characteristic reaction in the breakdown of photoreceptors during light depletion [ 1 , 86 ]. In the present study, we compared the chlorophyll content and photochemical efficiency (Fv/Fm) of leaf samples of DLS-42 and DLS-91 at three different phases of dark treatment ( Figure 2 A,B).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we compared the chlorophyll content and photochemical efficiency (Fv/Fm) of leaf samples of DLS-42 and DLS-91 at three different phases of dark treatment ( Figure 2 A,B). The rapid loss of chlorophyll and reduction in photochemical efficiency observed in DLS-91 may have been due to the breakdown of photosynthetic components leading to diminished photosynthesis during dark treatment [ 1 , 86 ]. Similarly, leaves of Arabidopsis and barley subjected to dark treatment have been reported to exhibit a decline in chlorophyll and the Fv/Fm ratio according to the progression of dark exposure [ 11 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main differences between the three different treatments are concentrated at 15-35DPA. The effects of CN treatment on grain weight were mainly concentrated in the spraying period (15 DPA) and the middle-late lling period (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). The grain weight in these two periods was signi cantly higher than that of CK.…”
Section: Grain Weight and Grain-lling Characteristic Parametersmentioning
confidence: 99%
“…The PCD of cereal crop's endosperm is greatly in uenced by endogenous hormones 28 . Previous studies have shown there is the interaction among the hormones, which constitute a very ne and complex regulatory network together with the external environment and their own developmental programs [29][30][31] . Furthermore, the main endogenous hormones ethylene and abscisic acid had signi cant effect on the endosperm PCD and grain lling process of cereal crops.…”
Section: Introductionmentioning
confidence: 99%